The Impact of Nuclear Energy Consumption on Economic Growth and CO2 Emissions in Selected Asian Economies - Batool, Komal; Akbar , Muhammad (Pakistan Journal of Humanities and Social Sciences, 2022)
Most countries' economic policies aim towards long-term growth in the economy. The economic growth has an effect on global warming and climate change, which are two of the biggest problems and worries in the world. Because of economic growth and civilization, the amount of carbon dioxide (CO2) and other greenhouse gases (GHG) in the air has gone up. In order to do this, the study used the Dumitrescu and Hurlin (D-H) and Common Correlated Effect Mean Group (CCE-MG) causality tests to look at how nuclear energy affected economic growth in some Asian countries from 1990 to 2017. The results of CCE-MG showed that developing countries in Asia used less renewable energy and nuclear energy than they thought they would. On the other side, the use of non-renewable energy had the negative effect on economic growth. Further, it was observed that the renewable energy had a positive effect on the amount of CO2 released in developing countries. Based on the results, the study suggested that the government and policymakers should focus on renewable energy sources to help them grow while at the same time putting in place environmental rules to protect the environment.